Case Report: A Troublesome Ophthalmic Artery Aneurysm - Meling, T. R.; Sorteberg, W.; Bakke, S. J.; Jacobsen, E. A.; Lane, P.; Vajkoczy, P. (Journal of Neurological Surgery Reports, 2014)
Objective and Importance When treating large unruptured ophthalmic artery (OA) aneurysms causing progressive blindness, surgical clipping is still the preferred method because aneurysm sac decompression may relieve optic nerve compression. However, endovascular treatment of OA aneurysms has made important progress with the introduction of stents. Although this development is welcomed, it also makes the choice of treatment strategy less straightforward than in the past, with the potential of missteps.Clinical Presentation A 56-year-old woman presented with a long history of progressive unilateral visual loss and magnetic resonance imaging showing a 20-mm left-sided OA aneurysm.Intervention Because of her long history of very poor visual acuity, we considered her left eye to be irredeemable and opted for endovascular therapy. The OA aneurysms was treated with stent and coils but continued to grow, threatening the contralateral eye. Because she failed internal carotid artery (ICA) balloon test occlusion, we performed a high-flow extracranial-intracranial bypass with proximal ICA occlusion in the neck. However, aneurysm growth continued due to persistent circulation through reversed blood flow in distal ICA down to the OA and the cavernous portion of the ICA. Due to progressive loss of her right eye vision, we surgically occluded the ICA proximal to the posterior communicating artery and excised the coiled, now giant, OA aneurysm. This improved her right eye vision, but her left eye was permanently blind.Conclusion This case report illustrates complications of the endovascular and surgical treatment of a large unruptured OA aneurysm.
Keywords: ophthalmic artery aneurysm; endovascular treatment; neurovascular surgery; complications